Power and influence: CEO power and the use of tactical influence - Ibn Twalh, Abdulaziz Awad; Alsolami, Hazaz Abdullah; Teoh, KennyGuan Cheng; Nurul Islam, Gazi Md. (Sciedu Press, 2016)
This paper describes how the CEO of an organization can effectively manage the organization by using the identified sources of power, and the various techniques of gaining power in an organization. Often, an organization fails because of insufficient attention paid to how power is managed and deployed. This paper identifies and discusses the power dynamics in organizations, the possible sources of political conflicts at work, and how to solve such issues when they arise. It also discusses the best influence tactics that can be wielded by a CEO to provide guidance, the direction that such influence should take and on which group of people. The authors suggest that the best way to manage employees as a CEO is by becoming a storyteller. This “storyteller” metaphor suggests that CEOs should always focus on creating friendly and interactive environments, rather than tense environments, in which the storyteller (CEO) always engages the audience and makes them feel at ease. It asserts that legitimate and coercive sources of power are no longer advantageous.